2015
DOI: 10.4236/fns.2015.65054
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Carvacrol on the Growth Performance, Hematological, Non-Specific Immune and Serum Biochemistry Parameters in Rainbow Trout (<i>Oncorhynchus mykiss</i>)

Abstract: The present study investigated the effects of phytoadditive carvacrol on growth performance, feed utilization, hematological, non-specific immune and serum biochemical parameters in rainbow trout (Oncorhynchus mykiss). In trial, 240 rainbow trout which had average weight of 10.79 ± 0.57 was used. Fish were divided into four groups before being fed for 60 days with 0, 1 (C1), 3 (C3) or 5 (C5) g/kg of carvacrol. There were no particular differences in the growth performance, feed utilization, whole body composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 20 publications
4
26
1
6
Order By: Relevance
“…Likewise, Yilmaz et al (2015) found no significant differences in the body composition of O. mykiss juveniles fed carvacrol-supplemented diets. Conversely, other studies have demonstrated the influence of dietary supplementation with oregano essential oil, or its active ingredients, on the body composition of different fish species.…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations
“…Likewise, Yilmaz et al (2015) found no significant differences in the body composition of O. mykiss juveniles fed carvacrol-supplemented diets. Conversely, other studies have demonstrated the influence of dietary supplementation with oregano essential oil, or its active ingredients, on the body composition of different fish species.…”
Section: Resultsmentioning
confidence: 86%
“…Likewise, no effect was observed on growth parameters in juveniles of Nile tilapia (Oreochromis niloticus) fed different essential oils, including oregano essential oil (CAMPAGNOLO et al, 2013). As well as there was no significant influence on the results in studies using supplementation with carvacrol (main active ingredient of oregano essential oil) in diets for O. niloticus (FRECCIA et al, 2014), sea bass (Dicentrarchus labrax) (VOLPATTI et al, 2014) and rainbow trout (Oncorhynchus mykiss) (YILMAZ et al, 2015). On the other hand, in contrast to the aforementioned studies, the inclusion of oregano essential oil in the diet resulted in positive effects on the performance of juvenile channel catfish (Ictalurus punctatus) (ZHENG et al, 2009), of O. mykiss (AHMADIFAR et al, 2011DILER et al, 2017), and of A. lacustres (=A.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ficus carica, is known to have antimicrobial (Ryu and Jung, 1999) and antioxidant effects (Yang et al, 2009). Recently, several studies have been conducted about the usage of medical plant extracts as prophylactic products as a result of their usage as feed additive in the general animal products and aquaculture, of increase in the growth, and of achievement of positive results (Goda, 2008;Zheng et al, 2009;Yilmaz et al, 2015). Nowadays in aquaculture, there is a need for specifying the in vivo effective doses of alternative agents, which are natural, reliable, antimicrobial, and not giving any harm to the ecosytem, and adding them to the sector.…”
Section: Introductionmentioning
confidence: 99%